The Pathogenicity of Soybean Mosaic Virus and Cowpea Mild Mottle Virus on Soybean Variety TGX 14428-2E - Aliyu, T. H.; Balogun, O. S.; Ayinla, I. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2015)
A greenhouse experiment was performed to investigate the pathogenicity of soybean mosaic virus (SMV) and cowpea mild mottle virus (CPMMV) on Soybean cultivar TGX 1448-2E. The viral isolates which served as the viral inoculum were extracted by homogenisation from infected leaves at the rate of 1 g, leaf sample to 5ml buffer solution. A total of 15 plastic pots were filled with sandy-loam soil previously steam-sterilized for 12 hours at 100oC. Four seeds of the soybean cultivar were sown in each plastic pot prior to mechanical inoculation 14 days after. Inoculation with the two viral inoculums and phosphate buffer solution which served as the control was carried out on 5 pots (20 plants) per treatment. The results indicated increasing disease severity for both viruses over time. However at the end of observation, plants inoculated with SMV manifested higher infection rate (14.1 %), followed by CPMMV (13.6 %) when compared with the control (8.6 %). The virus inoculated plants produced relatively short and reduced number of leaves compared to control. In terms of yield, SMV inoculated plants had reduced pod (11.5 g) and seed (3.9 g) weights in comparison to control (19.6 g and 3.9 g respectively). The results from the study showed that Soybean variety TGX1448-2E is susceptible to both viruses with SMV more pathogenic. This is an indication that adequate control measures for viruses should be deployed to increase soybean production with a view to improving farmer income and enhancing food security in Nigeria.